Penerapan Metode Hungarian pada Usaha Rumahan Kue Cincin untuk Meminimalkan Biaya Operasional : (Studi Kasus: UMKM Pak Sofwan) - Apriani Syahputri; Fadilah Aulia; Siti Izzati Sarah; Siti Salamah Br Ginting (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, including in the traditional culinary sector such as the home-based Kue Cincin Sofwan business. However, in its operations, inefficient division of worker tasks is often found, resulting in wasteful costs. This study aims to apply the Hungarian Method in determining optimal worker assignments in order to minimize operational costs. The study was conducted through a case study approach with observation, interview, and documentation techniques on four workers and four main types of work: kneading, molding, frying, and distributing cakes. Working time data was converted into costs, then analyzed using the Hungarian Method through row and column reduction steps and zero-based assignments in the matrix. . The results showed a 25% decrease in operational costs compared to the previous assignment system. The results of the analysis showed that optimal worker allocation resulted in assignments with lower total costs than the previous unstructured method. Thus, the application of the Hungarian Method has proven effective in helping MSMEs, especially home businesses, improve operational efficiency and cost savings. This study is expected to be a reference for similar business actors in managing human resources more efficiently and scientifically.